Evaluation of the running parameters of the polar cranes installed in the NPP reactor compartments during their control assembly - Pimshin Yuri I.; Zayarov Yuri V.; Pimshin Ivan Yu. (MATEC Web of Conferences, 2018)
The paper considers the basic principles of motion along the polar cranes circumference. The geometric parameters of the mutual turn of the crane running wheels are shown to be the critical features in the crane motion along the circumference. Noncompliance of the turn determines the transverse slippage of the crane running wheels, while the wheel shape affects only the elastic longitudinal slip. The consequence of slide and slippage is the railhead actuation on one side and the loss of the road stability when the crane moves. Stability of the road-holding rigidity ensures achievement of targeting accuracy of the load-gripping device. These parameters are the main operational characteristics which should be normalized and should be minimal in absolute terms.